Implementation of Chest Physiotherapy in Children with Tuberculosis to Manage Ineffective Airway Clearance - Nita Khikmatul Aeni; Murniati (Genius Journal, 2022)
Objective: This case study aims to describe the nursing care process and analyze the administration of chest physiotherapy to treat ineffective airway clearance in children diagnosed with tuberculosis. Method: This research is a case study research using random sampling technique for the sampling process. The samples used were children diagnosed with tuberculosis, being hospitalized, and experiencing ineffective airway clearance. The study was conducted in March 2022. Data collection used a nursing assessment format for children, a physical examination format, and an interview guide format. The nursing care process is carried out from the initial stage of assessment to evaluation. Result: The main complaint expressed was a fever that went up and down, often felt nauseated, coughed up phlegm that was difficult to expel. The data findings showed wheezing, cyanotic skin color, and an increase in respiratory rate and pulse. The patient experiences ineffective airway clearance. Effective chest and cough physiotherapy interventions were given for 3 days during the treatment period and showed that the results of walking clearance were not effectively resolved. This condition is seen from the phlegm that has come out, there are no additional breath sounds, the respiratory rate and pulse are within normal limits. Conclusion: The provision of effective chest physiotherapy and coughing interventions proved to be able to overcome ineffective airway clearance. Research recommendations to be able to combine alternative non-pharmacological techniques in overcoming ineffective airway clearance in children, especially with tuberculosis.